PENGARUH VARIETAS KACANG TANAH (Aracis hypogaea L.) DAN DOSIS PENGAPURAN TERHADAP PENYAKIT BUSUK BATANG Sclerotium rolfsii Sacc. PADA LAHAN GAMBUT - Chairudin Chairudin; Lola Adres Yanti; Paulina Zalukhu (Universitas Teuku Umar, 2018)
Peanut has high economic value because has high nutritions especially protein and fat, but the development of broad harvesting and peanut production for the last five years (2008-2012) continues to decrease. The main problem of the peanut low production are disease attacks S. rolfsii and the low broad harvesting. The drop of peanut production in Nusa Tenggara Barat causing harm caused by fungi S.rolfsii can reach 58,3 % per year. Peat is potential land to be developed to farming land. Peat has high acidity so fungi S. rolfsii would be easy to develop and resulted disease severity of peanut disease. Solution of this problem is the gift of lime. This study aims (1) to test the effect of dosages of lime to peanut resistance which was infected by rot stem S. rolfsii on peat land; (2) to study interaction of peanut varieties and dosage of lime to rot stem disease attacks S. rolfsii on peat land. This study used factorial block randomized design 2 x 3 with 3 replications. The studied factors were peanut varieties and the dosage of lime. The result showed that on the effect of varieties, the widest disease percentage was on Takar 2 variety on age 21, 28, 42, and 49 day after planting (DAP) that significant difference with Bison variety. The worth disease intensity was on Takar 2 variety that significant difference with Bison variety (on age 45 and 60 DAP). Key words: dosage of lime, peanut varieties, peat land, the sclerotia of Sclerotium rolfsii